Declines of ebony and ivory are inextricably linked in an African rainforest - Deblauwe, V.; Luskin, M.S.; Assola, S.D.; Hardy, O.J.; Jansen, S.; Loubières, C.; Mempong, G.G.; Ntsihe, J.M.; Ndjock, G.O; Kwecheu, E.R.O.; Powell, L.L.; Sonke, B.; et al. (American Association for the Advancement of Science, 2025)
Critically endangered African forest elephants preferentially eat fruits and disperse seeds of carbon-dense trees, including the highly valued and threatened African ebony. The illegal ivory trade has led to severe declines in elephant populations, but the long-term impacts on tree species are poorly understood. Using a comprehensive dataset including age-class, spatial, genetic, and experimental data, across a hunting pressure gradient, we show how paired declines in elephant and ebony populations are linked by a previously unrecognized mutualism in which elephant dung protects ebony seeds against seed predators. Disruption of this mutualism by poaching exacerbates seed predation by herbivores and was associated with a 68% reduction in small sapling recruitment. This threat to the survival of a valuable and iconic tree species raises concerns about the far-reaching consequences of forest elephant extermination.